Developing Religious Moderation in Millennial Santri: A Case Study at Ma’had al-Jami’ah UIN Cyber Syekh Nurjati Cirebon - Khaeriyah, Umamatul; Muthoharoh, Muthoharoh; El -’Izzah, Neily (Belajea: Jurnal Pendidikan Islam, 2025)
Islamic boarding schools have become centers for developing moderate ideas in a multicultural Indonesian society from various cultures, religions, races, ethnicities, and languages. Thus, Islamic boarding schools act as strategic educational institutions that form moderate santris that can positively maintain harmony and peace in society. This research aims to investigate how Ma’had Al-Jami’ah forms moderate millennial santris. This study used a case study research design using qualitative methodologies, with observation, in-depth interviews, and documentation as instruments. The study occurred at Ma’had Al-Jami’ah UIN Cyber Syekh Nurjati Cirebon, where the participants were santris of Ma’had Al-Jami’ah. The issue: This study investigates religious attitudes. The findings suggest that santris accept the condition of Ma’had facilities gracefully, behave politely and courteously, love local culture, like to help other people in Ma’had and outside environments, interact with friends from various backgrounds, act collaboratively in several activities, and are trained to live independently in the ma’had environment. Finally, Islamic boarding schools have a significant role in developing moderate santris. It can serve as a foundation for Islamic boarding schools to continue developing curricula and teaching techniques that effectively instill the values of religious moderation.